Beyond Digital Distraction: Surah al-‘Aṣr as a Qur’anic Framework for Time Ethics and Family Relations - Nur Safitri; Ihsan Nurmansyah; Muhammad Adam Abd. Azid (Elkuator Research and Publication, 2025)
The rapid expansion of digital technology has significantly transformed patterns of family communication, particularly through the phenomenon of phubbing, defined as the neglect of others’ presence due to excessive smartphone use. Within Muslim family contexts, phubbing has been identified as a contributing factor to the weakening of emotional bonds, the deterioration of communication quality, and the disruption of core familial functions. Although this phenomenon has been widely examined from psychological and sociological perspectives, studies employing Qur’anic frameworks to construct contextually grounded family ethics remain limited. This article seeks to reconstruct Surah al-ʿAṣr (Q. 103:1–3) as a Qur’anic ethical paradigm for addressing phubbing and relational disruption within families in the digital age. Employing Abdullah Saeed’s contextual tafsir methodology and a comprehensive literature review, this study integrates linguistic analysis, micro- and macro-contextual examinations, and comparative readings of classical, modern, and contemporary tafsir, which are subsequently situated within contemporary social realities. The findings demonstrate that Surah al-ʿAṣr can be recontextualized into three core ethical values: (1) the ethics of time management, which frames time and attention as moral and spiritual trusts; (2) the productive use of time through quality righteous deeds (ʿamal ṣāliḥ), manifested in relational presence and care within the family; and (3) the cultivation of a family communication culture grounded in tawāṣī bi al-ḥaqq and tawāṣī bi al-ṣabr, emphasizing empathetic dialogue and relational patience. Theoretically, this study contributes to Qur’anic scholarship by proposing a model of ethical recontextualization that bridges the normative message of Surah al-ʿAṣr with contemporary ethical challenges arising from digital culture. Practically, the findings suggest that addressing phubbing requires strengthening ethical awareness and fostering family communication rooted in Qur’anic values, rather than relying solely on technological regulation. [Disrupsi teknologi digital telah mengubah pola komunikasi keluarga secara signifikan, salah satunya melalui fenomena phubbing, yaitu perilaku mengabaikan kehadiran orang lain akibat keterlibatan berlebihan dengan smartphone. Dalam konteks keluarga Muslim, phubbing berkontribusi pada melemahnya relasi emosional, menurunnya kualitas komunikasi, dan potensi disintegrasi fungsi keluarga. Meskipun fenomena ini telah banyak dikaji dari perspektif psikologi dan sosiologi, kajian Al-Qur’an yang merumuskan kerangka etika keluarga secara kontekstual masih relatif terbatas. Artikel ini bertujuan merekonstruksi Surah al-‘Aṣr sebagai kerangka etika Qur’ani dalam merespons phubbing dan disrupsi relasi keluarga di era digital. Penelitian ini menggunakan pendekatan tafsir kontekstual Abdullah Saeed dengan metode kajian kepustakaan, meliputi analisis linguistik, telaah konteks mikro dan makro, serta analisis komparatif tafsir klasik, modern, dan kontemporer, yang kemudian dikontekstualisasikan dengan realitas sosial kekinian. Hasil penelitian menunjukkan bahwa Surah al-‘Aṣr dapat direkontekstualisasikan ke dalam tiga nilai etis utama: (1) etika pengelolaan waktu sebagai amanah moral dan spiritual, (2) pengisian waktu dengan amal ṣāliḥ berkualitas yang diwujudkan melalui kehadiran dan kepedulian relasional dalam keluarga, serta (3) pembangunan budaya komunikasi keluarga berbasis tawāṣī bi al-ḥaqq dan tawāṣī bi al-ṣabr yang menekankan dialog empatik dan kesabaran relasional. Secara teoretis, penelitian ini berkontribusi pada pengembangan studi Al-Qur’an dengan menawarkan model rekontekstualisasi etika yang menjembatani pesan normatif Surah al-‘Aṣr dan tantangan etika digital kontemporer. Secara praktis, temuan ini menegaskan bahwa penanganan phubbing memerlukan penguatan kesadaran etis dan budaya komunikasi keluarga berbasis nilai-nilai Qur’ani, bukan sekadar pengaturan teknologis.]